2021
DOI: 10.1371/journal.pone.0256970
|View full text |Cite
|
Sign up to set email alerts
|

No tillage and residue mulching method on bacterial community diversity regulation in a black soil region of Northeastern China

Abstract: Soil microorganisms are important components of agricultural ecosystems; they are important in agricultural soil nutrient cycle and are easily affected by soil tillage. The response of soil microbial community to tillage is very complex, and the effect of the no tillage and residue mulching method on soil microbial diversity remains unclear. In 2019, the soil was collected from an experimental field after 10 years of continuous cultivation in the black soil area of the Sanjiang Plain in Northeastern China. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 57 publications
(62 reference statements)
4
16
0
Order By: Relevance
“…The black soil area located in northeastern China has a total area of approximately 1.09 million square kilometers, which is one of the three largest black soil areas in the world. However, under the action of natural factors such as erosion, slabbing and salinization, this land has also experienced long-term exploitation by high-intensity rough farming activities, which has led to a gradual loss of organic matter content in black soils, changes in the area and structure of soils and decreases in soil consolidation, water retention and fertilization capacity in varying proportions, as well as decreases in ecological and economic benefits [ 42 , 43 , 44 ]. Liaoning Province is an important black soil distribution area in China and also a pilot province for STFFT promotion.…”
Section: Introductionmentioning
confidence: 99%
“…The black soil area located in northeastern China has a total area of approximately 1.09 million square kilometers, which is one of the three largest black soil areas in the world. However, under the action of natural factors such as erosion, slabbing and salinization, this land has also experienced long-term exploitation by high-intensity rough farming activities, which has led to a gradual loss of organic matter content in black soils, changes in the area and structure of soils and decreases in soil consolidation, water retention and fertilization capacity in varying proportions, as well as decreases in ecological and economic benefits [ 42 , 43 , 44 ]. Liaoning Province is an important black soil distribution area in China and also a pilot province for STFFT promotion.…”
Section: Introductionmentioning
confidence: 99%
“…Soil management practices, reduced tillage, mulching, and organic manures influence soil properties, which play a role in shaping the composition of soil bacterial and fungal communities [89][90][91]. In the study, after 3 years of continuous no-tillage, cover cropping and poultry litter treatment, a decrease in soil pH from 6.67 to ~5.6 over the years, was observed.…”
Section: Changes In Soil Physicochemical Propertiesmentioning
confidence: 76%
“…Our study showed that no tillage shifted soil mycobiome composition (species richness) closer to the one in the undisturbed soil under natural vegetation, most likely by altering physicochemical properties of the soil environment [ 63 ], thus expanding the opportunity space [ 57 ] for fungi surviving and thriving. As, by general consensus, species-richer fungal communities or naturally developed communities are regarded as “healthier” [ 64 ] in comparison with agriculturally used ones, our results support the notion that switching the long-term conventional tillage fields to the no-till ones can improve soil health [ 65 ] and ecosystem productivity.…”
Section: Discussionmentioning
confidence: 99%